An Indian experience of neurocognitive endophenotypic markers in unaffected first-degree relatives of schizophrenia patients - Solanki, Ram Kumar (Indian J Psychiatry, 2016)
CONTEXT: Multiple vulnerability genes interact with environmental factors to develop a range of phenotypes in the schizophrenia spectrum. Endophenotypes can help characterize the impact of risk genes by providing genetically relevant traits that are more complaisant than the behavioral symptoms that classify mental illness. AIMS: We aimed to investigate the neurocognitive endophenotypic markers for schizophrenia in Indian population. SETTINGS AND DESIGN: In a cross-sectional study, we assessed neurocognitive functioning in 40 unaffected first-degree relatives (FDR) of schizophrenia patients with an equal number of healthy controls. MATERIALS AND METHODS: FDR schizophrenia group was compared with the control group on measures of short-term memory, verbal working memory, auditory verbal memory on indices of immediate recall and recognition, visuospatial working memory, visual attention, and executive functions. RESULTS: The study found that FDR schizophrenia scored poorly on all tested measures of neurocognition except visual attention. On calculating composite score, we found that composite neurocognitive score better discriminated the FDR schizophrenia from the control group. CONCLUSIONS: Neurocognitive measures of short-term memory, verbal working memory, auditory verbal memory, visuospatial working memory, and executive functions significantly differentiate FDR of patients with schizophrenia from controls and can be considered as endophenotypic markers of schizophrenia in non-Caucasian population. The exactitude of this approach can be increased by calculating a composite neurocognitive score which combines various neurocognitive measures.